THE EFFECT OF FERMENTED PAPAYA (Carica papaya L.) LEAVES IN RATION ON THE CARCASS PIECES PERCENTAGE OF KAMPUNG CHICKEN (Gallus domesticus) - I M. D., Antara; Puger, A. W.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 9 No 3 (2021): Vol. 9 No. 3 Tahun 2021; September - December, 2021)
This study aimed to examine the effect of fermented papaya leaves in the ration on the carcass pieces percentage of kampung chicken, which was carried out for 8 weeks. The design used was a completely randomized design (CRD) which consisted of 4 treatments and 4 replications, each replication consisted of 3 kampung chickens. The treatments given were, A: Ration without fermented papaya leaves, B: Ration containing 10% fermented papaya leaves, C: Ration containing 15% fermented papaya leaves, D: Ration containing 20% ??fermented papaya leaves. The variables observed included slaughtered weight, carcass weight, carcass percentage, percentage of carcass pieces (chest, thighs, calves, back and wings). The results showed that the ration cantaining 10% fermented papaya leaves was able to significantly increase (P<0.05) by 15.78% in slaughtered weight and 19.05% in carcass weight. Slaughtered weight and carcass weight also increased significantly (P<0.05) with the ration containing 15% fermented papaya leaves by 19.26% and 20.04%, while the ration containing 20% fermented papaya leaves did not give significantly different results (P>0 0.05) on slaughtered weight, carcass weight, percentage of carcass and percentage of carcass pieces (chest, thighs, calves, back, wings). Based on the results of study, it could be concluded that the use of fermented papaya leaves in the ration level of 10-15% can increase the slaughtered weight and carcass weight but had no effect on the percentage of carcass and the percentage of carcass pieces (chest, thigh, calves back and wings) in native chickens. 10 weeks old.   Keywords: papaya leaves, kampung chicken, percentage of carcass pieces